2001
DOI: 10.1515/irm-2001-0105
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidative Deamination and Decarboxylation of L-Asparagine by Alkaline Permanganate: a Mechanistic Approach

Abstract: The kinetics of oxidative deamination and decarboxylation of L-asparagine (L-Aspg) by aqueous alkaline permanganate at constant ionic strength of 0.50 mol dm -3 were studied spectrophotometrically. The reaction exhibits first-order kinetics in [permanganate ion] and fractional-order dependences in [L-Aspg] and [alkali]. Initially added products such as aldehyde, ammonia and manganate have no significant effect on the rate of reaction. An increase in ionic strength and a decrease in dielectric constant of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Microbiologically mediated degradation of EDTA in circumneutral pHs also proceeds via the formation of ED3A, N,N′-ethylenediaminediacetic acid (EDDA), iminodiacetatic acid (IDA), and low-molecularweight compounds (9,10). Experiments with model compounds such as amino acids (e.g., [11][12][13][14] have shown that the reduction of permanganate by these species at high pHs proceeds via formation of manganate MnO4 2-, hypomanganate MnO4 3-(15), and finally MnO2 or mixed Mn(III)/Mn-(IV) solids (16). Identified reaction products formed upon the permanganate oxidation of amino acids and other model compounds include ammonia, oxalate, CO2, and traces of aldehydes (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Microbiologically mediated degradation of EDTA in circumneutral pHs also proceeds via the formation of ED3A, N,N′-ethylenediaminediacetic acid (EDDA), iminodiacetatic acid (IDA), and low-molecularweight compounds (9,10). Experiments with model compounds such as amino acids (e.g., [11][12][13][14] have shown that the reduction of permanganate by these species at high pHs proceeds via formation of manganate MnO4 2-, hypomanganate MnO4 3-(15), and finally MnO2 or mixed Mn(III)/Mn-(IV) solids (16). Identified reaction products formed upon the permanganate oxidation of amino acids and other model compounds include ammonia, oxalate, CO2, and traces of aldehydes (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators [8][9][10][11][12][13][14][15][16][17] have suggested that most of the oxidation reactions by permanganate ion in neutral and alkaline media proceed through intermediate complex formation between the oxidant and substrate. Spectroscopic evidence for such a complex was obtained from the UV-Vis spectra, Fig.…”
Section: Discussionmentioning
confidence: 99%